The Effect of A Boiled Betel Leaf and Turmeric on Vaginal Discharge in Women of Childbearing Age - Azzahroh, Putri; Salzabilla, Puspa; Bunga Tiara Carolin (Rajaki of Tulip Medika Publisher, 2024)
Vaginal discharge is the most common complaint in women of childbearing age, with 8 0% of cases occurring between the ages of 15 and 45 years. Physiological vaginal discharge is at risk of developing into pathological vaginal discharge and can lead to complications, such as vaginitis and cervicitis. Betel leaves have the potential to be a natural remedy because of the content of eugenol chemical compounds that can ward off the fungus candida albicans. Turmeric contains curcumin that inhibits growth and kills pathogenic bacteria and fungi. This study aims to determine the effect of betel leaf and turmeric decoction on vaginal discharge in women of childbearing age. Quasy-Experimental Research Pretest Posttest with Control Group Design. The number of respondents was 30 women of childbearing age who experienced pathological vaginal discharge, selected by purposive sampling technique. The instruments used were a whitish questionnaire and an observation sheet. The average vaginal discharge value of women of childbearing age in the intervention group was obtained with a pretest score of 3.80 and a posttest score of 2.13. The average rate of vaginal discharge of women of childbearing age in the control group had a pretest score of 4.27 and a posttest score of 4.13. In the Paired Sample T Test, the p-value of the intervention group was 0.000. In the Independent T Test, the mean difference between the posttest group was 2.00 and the p-value was 0.000. There is an effect of betel leaf decoction and turmeric on vaginal discharge in women of childbearing age.